A feminist Constituent: How to reform the Constitution with a gender perspective? Itziar Gómez Fernández (2017) Marcial Pons, Madrid, 205 pp. - Quispe Ponce, María Candelaria (2018)
In the wake traced by the feminist vindication, advocated by Olympia de Gouges in her classic Declaration of the Rights of Woman and the Citizen of 1791; Mary Wollstonecraft, in her work Vindication of the Rights of Woman, published in 1792; and more recently, in the positioning of the Feminist Network of Constitutional Law before the reform of the Constitution (2017); the basic premise from which the lawyer (advisor) of the Constitutional Court, Itziar Gómez Fernández, in Una Constituyente feminista: How to reform the Constitution with a gender perspective? is that the constituent process that gave birth to the Spanish Constitution of 1978 -currently in force- left aside half of the social being on which the "founding text" should act.